2024
DOI: 10.1038/s41598-023-50162-9
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between MALAT1 and TUG1 with dietary fatty acid quality indices on visceral adiposity index and body adiposity index

Niloufar Rasaei,
Fatemeh Gholami,
Mahsa Samadi
et al.

Abstract: We aimed to investigate the interaction between the transcript levels of taurine-upregulated gene 1 (TUG1) and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) and the Cholesterol-Saturated Fat Index (CSI) in relation to the visceral adiposity index (VAI) and body adiposity index (BAI). This cross-sectional study involved 346 women classified as obese and overweight, aged between 18 and 48 years. Dietary intake and the quality of dietary fat were assessed using a validated and reliable 147-item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, the transcription levels of MALAT1 and TUG1 showed a positive correlation with major lipogenic and adipogenic genes [121], and thus the authors suggested possible roles of MALAT1 and TUG1 in obesity. Moreover, Rasaei et al [122] suggested that there may be a positive interaction effect between MALAT1 transcription levels and the cholesterol/saturated fat index, which impacts the visceral adiposity index and body adiposity index among overweight and obese women. However, it was found that MALAT1 expression was significantly reduced in atherosclerotic plaques.…”
Section: Role Of Malat1 In Processes Associated With Fat Deposition A...mentioning
confidence: 99%
“…However, the transcription levels of MALAT1 and TUG1 showed a positive correlation with major lipogenic and adipogenic genes [121], and thus the authors suggested possible roles of MALAT1 and TUG1 in obesity. Moreover, Rasaei et al [122] suggested that there may be a positive interaction effect between MALAT1 transcription levels and the cholesterol/saturated fat index, which impacts the visceral adiposity index and body adiposity index among overweight and obese women. However, it was found that MALAT1 expression was significantly reduced in atherosclerotic plaques.…”
Section: Role Of Malat1 In Processes Associated With Fat Deposition A...mentioning
confidence: 99%
“…As a multifactorial disease, environmental conditions such as dietary intake and genetic variations are involved in its pathogenesis [ 10 15 ]. Apart from a positive connection between total fat intake and risk of MetS, as reported in a Japanese-Brazilian population, it is crucial to mention that dietary fat quality is also of utmost importance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%